The epidemiology of schoolboy rugby injuries - Roux, Charles E (Department of Medicine, 2017)
Schoolboy rugby injuries are a cause for concern in medical and non-medical circles, but few scientific investigations into their nature and frequency have been undertaken. The majority of reported rugby injury surveys are retrospective, have considered only specific injuries, or have reported only those seen at one location. Also, most studies have not distinguished minor injuries from major injuries. A pilot study conducted at one school in Cape Town during the 1982 rugby season, showed clear patterns of injury related to the age of players, their level of competition, playing position, the stage of the rugby season and the phase of play at the time of injury (Nathan et al. 198 3) . The studies as reported in this thesis were designed as a comprehensive follow-up study. The research methods and definition were similar but a much larger sample was studied and new areas not covered by the pilot study were introduced. During two 18-week seasons, in which approximately 4 700 players from 26 high schools played 6766 rugby matches, 905 players were prevented from participating in rugby for at least one week due to injury. The incidence and nature of injuries occurring to these players were followed in a prospective study and results were analysed for: (i) overall number and incidence of injured players; (ii) age-group and playing level; (iii) time of the season; (iv) phase of play; (v) playing position; (vi) type of injury; (vii) anatomical site; (viii) specific diagnoses; (ix) match vs practice injuries; (x) number of days off rugby; and (xi) medical treatment. The use of correspondence as a survey method resulted in 40 to 50% of injuries not being reported over the two-year period of the study. It appeared that the most accurate method of data collection was direct personal contact between the researcher and the injured player.